Internet strategy : the road to web services solutions - Guah, Matthew W., 1963-; Currie, Wendy, 1960- (Hershey, PA : IRM Press, 2006)
'This book tells you how to create, execute and evolve a customer-centric approach for your Internet-based management strategy'--Provided by publisher.
PS UNIKEB
Includes bibliographical references and index.
Keywords: Business enterprises -- Computer networks -- Management; Information technology -- Management; Web services -- Management